Analysis of Communication Patterns in Romantic Relationships Among the Millennial Generation - Basri, Ademiar Frederick (Kampret Journal, 2024)
This research investigates communication patterns in romantic relationships among the millennial generation, characterized by their extensive use of digital technology and evolving societal norms. Employing a mixed-methods approach, the study combines quantitative surveys and qualitative interviews to explore how millennials navigate their interpersonal dynamics. The findings reveal that digital communication platforms, such as text messaging and social media, play a central role in millennial relationships, facilitating frequent interaction but also presenting challenges like misunderstandings and conflicts due to the lack of non-verbal cues. Millennials exhibit a strong preference for authenticity and transparency, valuing open dialogue and emotional honesty, which aligns with their increased awareness of mental health issues. The study also highlights a shift towards egalitarian relationship models, with millennials seeking equal partnerships and collaborative conflict resolution. However, economic pressures and financial discussions remain significant challenges, impacting relationship stability. The research acknowledges limitations such as potential sampling biases and the dynamic nature of digital communication. Overall, this study provides insights into modern communication practices, offering implications for relationship dynamics, counseling approaches, and societal norms, and emphasizes the importance of adapting strategies to support healthy and fulfilling romantic relationships in today’s evolving social landscape.